Technical Efficiency Analysis of Cayenne Pepper Production (Case in Pagu, Kediri, East Java) - TITIS SURYA MAHA RIANTI (Agricultural Socio-Economics Journal, 2018)
Low productivity due to the inability of farmers to allocate inputs and technology in full, resulting in lower of production. The present study has estimated the technical and scale efficiencies of cayenne pepper producing, found out the trend production of farmers and knew the projected inputs that must be adopted by farmers. The study is in Pagu village, Pagu Distric, Kediri Regency, Province of East Java. Primary data collected by interview cayenne farmers who became member of the farmers group. The data was analyzed with Data Envelopment Analysis (DEA) with VRS assumption and input-oriented.  The results show that cayenne pepper farming on the site research technically inefficient (CRSTE = 0,482) due to the low efficiency of scale (SE = 0,509), while the value of pure efficiency already high enough (VRSTE = 0,947). There are 4 farmers with SE = 1 and 60 farmers with SE < 1. Most of the farms have been observed have increasing return to scale trend production.